Periodontal ligament stem cell colony-forming units of fluorosed and nonfluorosed teeth: An in vitro study - Vangara Aditya; Kharidhi Laxman Vandana (Wolters Kluwer Medknow Publications, 2024)
Introduction: The continued quest for extracting possible differences in the colony forming units (CFUs) of periodontal ligament stem cells (PDLSCs) between fluorosed and nonfluorosed, led to the current original project to evaluate if any such difference exists. Materials and Methods: For this study, the soft tissues adhering to eight healthy fluorosed and seven nonfluorosed extracted teeth were scraped using a curette. Results: The results of this study demonstrate similar CFUs by both fluorosed and nonfluorosed PDLSCs (P = 0.97), but nonfluorosed PDLSCs showed higher CFUs. Moreover, this is the first study where CFUs on PDSLCs were compared between fluorosed and nonfluorosed groups. Conclusion: This would influence the regeneration or renewal capacity of PDLSCs following treatment or on the physiologic basis, respectively. This is the first study of its kind; therefore, further studies are in progress on age-related changes in PDLSCs to evaluate the potential markers and various tissue-forming abilities.